Designing and evaluating multi-representational learning environments for primary mathematics - Ainsworth, Shaaron E. (1997)
This thesis reports the design and evaluation of multi-representational learning environments that teach aspects of number sense. COPPERS is concerned with children's belief that mathematical problems can have only a single correct answer. CENTS addresses the skills and knowledge required for successful computational estimation.